Expressing excessive love feelings towards teachers (female) and its effects on behavior In the city of Al-Ahsa, Saudi Arabia - Almutair, Eman Fahad (Journal of Educational and Psychological Sciences, 2019)
This study aimed to identify the reasons ofexpressing excessive love feelings towards teachers (female) and its effects on behavior, in Al-Ahsa cityin Saudi Arabia.The researcher used the descriptive approach, and the study toolswere an interview and questionnaire distributed to a sample of (23) female students of the twenty-second school in Al-Ahsa. With the data processing method (SPSS), the study revealed a number of results; the most important of them, students who suffer from behavioral problems in the primary stage have a lack of love because of their parents, and that there is a relationship between the number of children and the educational qualification in the exposure to behavioral problems. Based on the results, the study suggested a number of recommendations, the most important of them are: activating the role of the psychological to guide students who suffer from behavioral problems in primary stage, the study also recommended involving students with problems in the social, sports, artistic and cultural activities of the school.